Human Factors and their Influence on Software Development Teams - A Tertiary Study - Dutra, Eliezer; Diirr, Bruna; Santos, Gleison (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Background: Software organizations increasingly need developers with high skills for social interactions. Managers, leaders, and academics need to know the human factors influencing the individuals, the development team, and the software project activities. Despite the increasing number of secondary studies about human factors in Software Engineering (SE) and in Agile Software Development (ASD), there is no study synthesizing which human factors influence software development without a specific perspective from SE or human factor thematic. Objective: We aim to summarise human factors and their influence on SE development teams and ASD teams. Method: We executed a tertiary study. We used thematic analysis to examine the resulting data. Results: We found 29 systematic literature reviews and systematic mapping studies addressing the human perspective in SE teams. We identified 101 human factors and 79 influences grouped in 4 categories (Team member, Team, Project, and Organization). Also, we identified 71 human factors and 60 influences on ASD. The most investigated human factors are Communication, Collaboration, Knowledge, and Motivation. Conclusions: The identified human factors and their influences can be considered most significant by software organizations, researchers, and academics in SE practices. Based on our results, practitioners might propose activities that enhance human capital behaviors that influence individual motivation, agile mindset, team climate, software quality, or agile transition in traditional organizations.